Financial Literacy And Financial Inclusion Strategy Model As Leverage Welfare Of Industrial Community Tourism Regency Of Gresik East Java - Ratnawati, Hj. Tri; Rohmasari, Fatma; Lokajaya, I Nyoman (Archives of Business Research, 2017)
Small industries over the past few years business conditions have not shown significant progress. Small industries have problems in the field of finance that is not able to separate between business finances with household finances, not having financial planning including business investment, not optimizing in utilizing banking facilities. The hypothesis of the research is H1: Financial literacy and financial inclusion have significant effect to society's welfare is, H2: Significant financial literacy indicator is old age, financial behavior and self control, H3: Significant financial inclusion indicator is banking facility, banking service and product banking H4: A significant indicator of society welfare is the economic and viable needs of the economy. The result of hypotheses shows that the relationship between Financial Literacy by using indicators of Old Age, Financial Behavior, Self Control on Society welfare is significant with T-statistics of 19.471 (> 1,966). Financial Inclusion using Banking Facility indicators, Banking Services and Banking Products is not significant with T-statistics 1,218 (1,966). Financial Literacy measured using the old age which has a value of 0.681> 0.50, Financial Literacy as measured by using Financial Behavior which has a value of 0.893> 0.50, Financial Literacy as measured by using Self Control has a value of 0.752> 0.50. Financial Inclusion as measured by using Banking Facility that has a value of 0.838> 0.50, Financial Inclusion as measured by Banking Services which has a value of 0.861> 0.50, and Financial Inclusion as measured by using Banking Products that have a value of 0.980> 0, 50. The society welfare variable measured by using life requirement has a value of 0.925> 0.50 and measured by using Mapan Ekonomi has a value of 0.932> 0.50.